Beliefs About Worry and Pain Amongst Adolescents With and Without Chronic Pain. (2nd November 2021) - Wainwright, Elaine; Jordan, Abbie; Fisher, Emma; Wilson, Charlotte; Mullen, Darragh; Madhavakkannan, Harini
Abstract: Objective: To explore beliefs about worries, beliefs about pain, and worries about pain held by adolescents with and without chronic pain. Methods: Adolescents with and without chronic pain aged 14–19 completed an online survey with free text questions about pain and worry. We collected demographics and used the Penn State Worry Questionnaire and Pain Catastrophizing Scale for Children to contextualize the qualitative data, which was analyzed with reflexive thematic analysis. Results: Eighty-one participants completed the survey, 36 with chronic pain and 45 without (mean age: 16.73). Compared to adolescents without chronic pain, adolescents living with chronic pain reported significantly higher general worry and pain catastrophizing. Thematic analysis generated two themes, "Worry changes perceptions of selfhood" and "Pain changes perceptions of selfhood." Each theme comprised two sub-themes showing how current and future identity trajectories were distorted by worry and pain. The theme "Pain changes perceptions of selfhood" also included a third sub-theme: "Pain impedes future working choices." Worry content as well as process was problematic in all adolescents. Adolescents experiencing chronic pain had specific, additional worries that pain reduces future career progression. These worries appeared highly salient and challenging. Conclusions: Adolescents may need greater support in recognizing worry as part of normative development. Adolescents in pain may benefit from specific support identifying and reducing how pain-related worries interact with their futures and careers, and from school-based and vocational interventions to reduce the realistic risks they face negotiating modern labor markets.